The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/rs14010063
|View full text |Cite
|
Sign up to set email alerts
|

Using Remote Sensing and Machine Learning to Locate Groundwater Discharge to Salmon-Bearing Streams

Abstract: We hypothesized topographic features alone could be used to locate groundwater discharge, but only where diagnostic topographic signatures could first be identified through the use of limited field observations and geologic data. We built a geodatabase from geologic and topographic data, with the geologic data only covering ~40% of the study area and topographic data derived from airborne LiDAR covering the entire study area. We identified two types of groundwater discharge: shallow hillslope groundwater disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…At the study sites, the locations of the cold springs did not conform to the surface topography (Figure 2). Although there are catchments where the topography can be used to predict the location of groundwater discharge zones (Gerlach et al, 2022;Leach et al, 2017), no correspondence between the surface topography and aquifer boundaries has been reported for Quaternary volcanic catchments (Fujimoto et al, 2016;Jefferson et al, 2006) and volcanic ash plateaus (Ikeda et al, 1999) similar to our sites, which can be attributed to the high subsurface permeability. Thus, our results demonstrate the importance of field surveys for mapping springs at sites underlain by a highly permeable geology.…”
Section: Merits Of Temperature Mapping Using Tir Videocontrasting
confidence: 59%
“…At the study sites, the locations of the cold springs did not conform to the surface topography (Figure 2). Although there are catchments where the topography can be used to predict the location of groundwater discharge zones (Gerlach et al, 2022;Leach et al, 2017), no correspondence between the surface topography and aquifer boundaries has been reported for Quaternary volcanic catchments (Fujimoto et al, 2016;Jefferson et al, 2006) and volcanic ash plateaus (Ikeda et al, 1999) similar to our sites, which can be attributed to the high subsurface permeability. Thus, our results demonstrate the importance of field surveys for mapping springs at sites underlain by a highly permeable geology.…”
Section: Merits Of Temperature Mapping Using Tir Videocontrasting
confidence: 59%
“…Machine learning and remote sensing combinations have been used to identify the location of thermal refuges and GW-SW interaction zones in numerous rivers (e.g., [17,[42][43][44]). In these studies, key landscape parameters (e.g., channel confinement, location of dry valleys) have been noted as potential predictors for the location of thermal refuges.…”
Section: Discussionmentioning
confidence: 99%
“…Surface landforms have long been invoked to conceptually explain spatial patterns of groundwater connectivity to surface waters (Winter et al, 1998). Locally, steep streambanks or streambed slopes can cut across hydraulic gradients and create groundwater discharge across the land surface, while high stream curvature can cause the convergence of groundwater flow paths to streams (Eschbach et al, 2017; Gerlach et al, 2022; Wawrzyniak et al, 2016). At the valley scale, the degree of channel confinement can control the prevalence of groundwater discharge, with partially confined valleys having the highest prevalence of streambank groundwater discharge relative to confined or unconfined settings (Dugdale et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While surface topography can exert strong controls on the spatial patterning of groundwater discharge, characteristics of underlying soils and bedrock geology are important as well. Gerlach et al (2022) found that the depths and locations of water bearing geologic formations derived from borehole data predicted the occurrence of groundwater discharges across several salmon bearing streams in Alaska, USA. Gerlach et al (2022) also found that the occurrence of bedrock outcrops was important in creating hillslope and streambank discharge features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation